Downregulated Expression of linc-ROR in Gastric Cancer and Its Potential Diagnostic and Prognosis Value. (25th October 2020) - Yu, Xiuchong; Ding, Haixiang; Shi, Yijiu; Yang, Liangwei; Zhou, Jiaming; Yan, Zhilong; Xiao, Bingxiu
Abstract : Background . Gastric cancer (GC) is one of the global mortality diseases and has a poor prognosis due to the lack of ideal tumor biomarkers. Numerous studies have shown that long noncoding RNAs (lncRNAs) can affect the occurrence and development of cancer through a variety of signaling pathways. The abnormal expression and specificity of lncRNAs in tumors make them potential biomarkers of cancers. Nevertheless, the diagnostic roles of lncRNAs in GC have been poorly understood. So this study focuses on the clinical diagnostic value of lncRNAs in GC. Materials and Methods . Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was used to investigate the expression of the linc-ROR (long intergenic noncoding RNA, regulator of reprogramming) in 105 paired GC tissues and adjacent normal tissues. Receiver operating characteristic (ROC) curve and area under the curve (AUC) were established to assess the diagnostic value of linc-ROR. The relationship between expression of linc-ROR and clinicopathological factors of patients with GC was further explored. Kaplan-Meier analysis was performed to evaluate the prognostic value of linc-ROR expression. Results . The linc-ROR expression level was significantly decreased in GC tissues compared with its adjacent nontumor tissues (n = 105, P < 0.001 ). We also discovered that linc-ROR was evidently downregulated in 68.6% (72/105) of GC tissues. The AUC's value of linc-ROR was up to 0.6495, with sensitivity and specificity of 0.7524 and 0.5143, respectively. Intriguingly, the linc-ROR expression levels were obviously associated with tumor differentiation (P = 0.004 ). Notably, the overall survival rate of GC patients with high expression of linc-ROR was significantly higher than those with low expression. Conclusion . Our data revealed that linc-ROR has clinical potential as a biomarker for the diagnosis of GC and assessment of its prognosis.